The Impact Of Preventive Medications And Factors Related To Acute Ischemic Stroke On Outcomes : Multimodal Preventive Medication Approach - Al-Jabi, Samah W. A. Zyoud (2011)
Acute ischemic stroke is a global health problem and is among the leading causes of morbidity and mortality. As prevention is considered the mainstay of management for acute ischemic stroke, knowledge should be highlighted regarding the scientific evidence behind the use of preventive medications and their impact on patients’ outcomes. The objective of the study is to evaluate the impact of the previous use of angiotensin-converting enzyme inhibitor (ACEI), antiplatelet and statin, either alone or in combinations on reducing in-hospital mortality rates, improving functional status at discharge and reducing complications after ischemic stroke. In addition, the independent factors associated with the occurrence of these ischemic stroke outcomes have been investigated. An observational retrospective cohort design was used for all acute ischemic stroke patients admitted to Hospital Pulau Pinang during the period from January 1st 2008 to June 30th 2009. Data included socio-demographic characteristics, clinical characteristics, and previous medication classes, with particular attention being paid to antiplatelets, ACEIs and statins. Impact of the previous use of these medications on ischemic stroke outcomes included: the in-hospital mortality rate, a good functional status as defined by the Barthel Index (BI) > 75, and post-stroke complications, was evaluated after controlling for other variables (i.e. socio-demographic, clinical characteristics, risk factors and other medications) that might have confounded the effects of these preventive medications on ischemic stroke outcomes.